A Retrospective Analysis on Prevalence of Multiple Myeloma in Young patients with presentation of Backache - Nazia Farooq, Ahmad Naeem Akhtar, Muhammad Rizwan, Sonia Tahir, Hira Tariq, Anam Tariq (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the prevalence of Multiple Myeloma in young patients. Study design: Retrospective study Study duration: 2009 to 2020 Methodology: Thirty six patients with diagnosis of Multiple Myeloma out of 258 bone marrows were selected for this study. All inclusion and exclusion criteria were followed. Results: Results showed that the prevalence of disease in this group was mostly in 4th and 5th decades of life with primary complaint at the time of presentation was backache. Conclusion: Patients with history of chronic backache should be taken seriously as it is one of the major complaints at time of presentation with Myeloma. Non invasive procedures must be followed by bone marrow examination to support the diagnosis. Keywords: Multiple myeloma, backache, clonal disorder, bone marrow